KAJIAN STILISTIKA-PESANTREN PADA WASIAT RENUNGAN MASA PENGALAMAN BARU TGKH. ZAINUDDIN ABDUL MAJID - Ernaliana, Ernaliana; Rusdiawan, Rusdiawan; Saharudin, Saharudin (Jurnal Ilmiah Mandala Education (JIME), 2021)
The research aims to analyze the islamic boarding school language and the meaning of Zainuddin Abdul Majid poems with a literature study and analyzed using content analysis methodology by using the semiotic perspective of Charles Sanders Peirce theory. The results of the study found several things including: 1) the poems used a lot of islamic typical words/phrases, namely key words in Islamic treasures that were identical to Arabic; 2) the form of words/phrases Islamic typical words which the author used tended to be simple, namely from 50 words/phrases. typical phrases of Islamic typical are 25 elements of icons, 20 elements of indexes, and 5 elements of symbols, 3) The typical words/phrases of islamic in poetry have different meanings according to the text and context.